Oro-dental manifestations of eating disorders: a systematic review - Leoluca Valeriani; Francesco Frigerio; Claudia Piciocchi; Gabriela Piana; Marco Montevecchi; Lorenzo Maria Donini; Edoardo Mocini (Journal of Eating Disorders, 2024)
Abstract Background Eating disorders (EDs) pose a significant risk to health, especially when not diagnosed early. For several years EDs and oral health has been extensively studied, and now it is quite clear the existence of a correlation between specific oral manifestations and these disorders. While these oral signs could potentially aid early diagnosis of EDs, their identification and the eventual establishment of a correlation is currently heavily limited to the clinician’s experience. The present systematic review critically examines existing literature, offering an updated overview of oro-dental manifestations associated with EDs. Method MEDLINE (via PubMed), Web of Science, Scopus, and grey literature were searched, and relevant epidemiological comparative studies were screened using the Rayyan software. No limitations have been imposed on the research regarding oro-dental outcomes, encompassing all medically diagnosed EDs. The quality of the studies was valuated using AXIS appraisal tool for cross-sectional studies. Result Out of 3990 studies, 32 fulfilled the eligibility criteria and were included in the synthesis. The identified eating disorders include Anorexia Nervosa, Bulimia Nervosa and/or Eating Disorders Not Otherwise Specified, predominantly among female subjects, primarily originating from Europe. The evaluated oro-dental outcomes include dental erosion, caries, saliva assessment, hygiene-periodontal parameters, and mucosal tissue appearance. The association with erosion is confirmed while gingival recession, dentinal hypersensitivity, salivary flow thresholds and aspects relating to oral pathology are receiving increasing support from emerging evidence. Discussion This trend emphasizes the critical role of the complete intraoral examination to detect significant oro-dental signs that may indicate the onset of an ED.